Integrated miRNA and mRNA expression profiling in response to eriodictyol in human endothelial cells - Lee, Seung Eun; Park, Hye Rim; Yun, Hong Duck; Cho, Jeong-Je; Ahn, Hyun-Jong; Park, Cheung-Seog; Park, Yong Seek (Biochip journal, 2017)
Eriodictyol, a flavonoid commonly found in citrus fruits, shows neurotrophic, antioxidant, anti- inflammatory, and anti-cancer effects under diverse pathophysiological conditions such as vascular diseases. In this study, we evaluated whether eriodictyol modulates miRNA and mRNA expression. Using microarray analysis, we examined miRNA and mRNA expression in human endothelial cells treated with 10 μM of eriodictyol for 24 h. Using numerous bioinformatic systems, we evaluated the signatures of the potential biological processes and signaling pathways. Our results provide insight into the underlying molecular mechanisms of action of eriodictyol and suggest that eriodictyol can be used for therapeutic intervention in vascular disease.